No less than victory : a novel of World War II - Shaara, Jeff, 1952- (Ballantine Books, 2009)
After the success of the Normandy invasion, the Allied commanders are buoyantly confident that the war in Europe will be over in a matter of weeks, that Hitler and his battered army have no other option than surrender. But despite the advice of his best military minds, Hitler will hear no talk of defeat. In mid-December 1944, the Germans launch a desperate and ruthless counteroffensive in the Ardennes forest. As American commanders respond to the stunning challenge, the German spear is finally blunted.